Wide Variation of Squeezing Force and Dispensing Time Interval among Eyedropper Bottles - Kenji Kashiwagi (Journal of Ophthalmology)
Purpose. We aimed to investigate squeezing force and dispensing time interval of the first and second eye drops among a variety of eyedropper bottles and to clarify associated factors within these parameters. Methods. A total of 87 eyedropper bottles were involved in this study. We developed a squeezing force measuring system consisting of a syringe pump, digital force gauge, and custom-made test stand to measure the squeezing force and dispensing interval. The eyedropper bottle was housed in the system vertically, and measurements were repeated five times. We investigated the differences in squeezing force and dispensing interval by categories, including those that targeted ocular disease, brand or generic eyedroppers, shapes of eyedropper bottles, and the presence of a membrane filter inside the tip of the eyedropper bottle. Results. The mean squeezing forces of the first drop and the second drops were 8.3 ± 3.0 N and 10.4 ± 3.2 N, respectively. Both squeezing forces had a wide variation of more than threefold. A mean interval between the first and second drops was 3.1 ± 1.2 sec with a maximum difference of more than sevenfold. Round shapes of eyedropper bottles and the presence of filter membranes significantly increased the squeezing force. Conclusions. The squeezing force of eyedropper bottles was very wide, which may affect proper eye drop instillation. Unification of eyedropper bottles or developing mechanical aids may be useful for proper eye drop treatment.